The use of shot wheat (Т.Sphaerococcum) in the winter bread wheat breeding to improve quality - B. A. Goldvarg; M. V. Boktaev; A. N. Borovik (Зерновое хозяйство России)
The current paper has presented the study results of grain productivity and quality of the winter bread wheat lines developed on the basis of T. Sphaerococcum at the ‘NCG named after P.P. Lukyanenko’ in the soil and climatic conditions of the Republic of Kalmykia. The purpose of the current work was to study productivity and quality of the winter bread wheat lines, hybridized from the crossing of two varieties. The trials were laid in two stages in 4-fold repetition with a sequential arrangement of the variants of the trial with the CH-16 seeder. The accounting plot area was 50 m2 . The seeding rate was 300 pcs. of germinating seeds per 1 m2 . On average, through three years of the study in weedfree fallow, the productivity of the winter bread wheat lines, developed on the basis of T. Sphaerococcum on the experimental field of the KRAI, affiliate of the FSBSI “PKAFRC RAS” (village of Troitskoe) was 3.25 t/ha. The largest mean productivity through three years (3.37 t/ha) was produced by the line ‘661sv-30’, which exceeded the standard on 0.36 t/ha, the excess over the variety ‘Praskovya’ was 0.64 t/ha. The study has confirmed the formation of the best values of grain quality by the shot wheat variety ‘Praskovya’. The protein and gluten content were on 1.8% and on 4.9% higher than that of the standard wheat variety ‘Bair’. The potential for high quality shot wheat grain can be successfully introduced into the bread wheat breeding material. The developed bread wheat lines ‘989sv-7’, ‘661sv-30’ and ‘661sv-39’ stably and reliably exceeded the standard variety in productivity, forming grain quality similar to that of the variety ‘Praskovya’. The line ‘989sv-7’ has been sent to the State Variety Testing under the name ‘Flash’, the line ‘661sv-30’ under the title ‘Khit’ and the line ‘661sv-39’ under the name ‘Pesnya’.